The Role of Modern Management Tools in Enhancing the Activity of Local Groups - Experiences of some Arab Countries with Reference to AlgerianCase - - بوعلاقة نورة (Milev Journal of Research and Studies, 2020)
The study aims to know the role of modern management tools in enhancing the work of local groups, by studying and analyzing the various tools that indicate the extent of interest of groups in the application of this type, especially as they are now receiving a great and increasing interest in various countries in general and Algeria in particular, In line with the requirements of the reality that pushed countries to the need to achieve progress and strengthen their fields of activity, and on this basis this study was based on determining the nature of the relationship that links the topic of local groups to the various tools and mechanisms used in the conduct of their performance, given that these are the last to form the main axis in Study this topic, and the ultimate goal to promote the activity of local communities and prosperity, The study found that enhancing the work of local groups contributed greatly to achieving a qualitative shift in the activity of groups, In addition, the success of local development programs requires greater encouragement for individual workers involved in achieving local development.